Azoxystrobin exposure impairs meiotic maturation by disturbing spindle formation in mouse oocytes - Gao, Wen; Zhang, Chen; Li, Bichun; Oh, Jeong Su (Frontiers in Cell and Developmental Biology, 2022)
Fungicides are a type of pesticide used to protect plants and crops from pathogenic fungi. Azoxystrobin (AZO), a natural methoxyacrylate derived from strobilurin, is one of the most widely used fungicides in agriculture. AZO exerts its fungicidal activity by inhibiting mitochondrial respiration, but its cytotoxicity to mammalian oocytes has not been studied. In this study, we investigated the effect of AZO exposure on mouse oocyte maturation to elucidate the underlying mechanisms of its possible reproductive toxicity. We found that AZO exposure disturbed meiotic maturation by impairing spindle formation and chromosome alignment, which was associated with decreased microtubule organizing center (MTOC) integrity. Moreover, AZO exposure induced abnormal mitochondrial distribution and increased oxidative stress. The AZO-induced toxicity to oocytes was relieved by melatonin supplementation during meiotic maturation. Therefore, our results suggest that AZO exposure impairs oocyte maturation not only by increasing oxidative stress and mitochondrial dysfunction, but also by decreasing MTOC integrity and subsequent spindle formation and chromosome alignment.